Structural conditions, social networks, and the HIV vulnerability among Indonesian male labour migrants and motorbike taxi drivers - Paul Russell Ward; Nelsensius Klau Fauk (International Journal for Equity in Health)
Abstract Background The Indonesian National AIDS report reveals that the percentage of HIV cases in the country is significantly higher in men compared to women, which is contrary to global AIDS data. Using a conceptual model of how social networks impact health, this paper describes how structural conditions, such as poverty, lack of job opportunities, and lack of income shaped the social networks of Indonesian men. It also describes how these social networks created opportunities for various social mechanisms, including social influence, peer pressure, and intimate contact, that facilitated HIV infection through different behavioural pathways, such as unprotected sex with multiple partners and injecting drug use (IDU) practices. Methods A qualitative design using face-to-face in-depth interviews was employed to collect data from heterosexual male participants (n = 25) in Yogyakarta municipality and Belu district, Indonesia. Participants were former labour migrants and previously or currently (at the time of the study) motorbike taxi (ojek) drivers. They were recruited using the snowball sampling technique, starting from two HIV clinics in the study settings. Data were analysed thematically guided by a qualitative data analysis framework. Results The findings highlight the significance of structural conditions, such as poverty, poor family conditions, precarious employment, and lack of income, which contributed to shaping the men’s social networks through their occupations as labour migrants and ojekdrivers. Involvement in these occupations allowed them to become acquainted with fellow labour migrants and ojek drivers, leading to cohabitation in the same shelters or areas and daily interactions, which fostered the development of social networks among them. These social networks then provided opportunities for various social mechanisms, including social influence through peer pressure and person-to-person contact. The influence and pressure experienced by the participants were reflected in their behaviours related to sex, condom use, and IDU, ultimately contributing to the transmission of HIV among them. Conclusions The findings underscore the importance of social network peer interventions that consider the dynamics of these networks. Such interventions have been shown to be effective in reducing HIV-risk behaviours and transmission, as well as in promoting HIV prevention and treatment among diverse population groups.